Culture, Ritual and Revolution in Vietnam, 1st edition - Malarney, Shaun Kingsley (Routledge, 2020)
Originally published in 2002 Culture, Ritual and Revolution in Vietnam is a study of the history and consequences of the revolutionary campaign to transform culture and ritual in northern Vietnam. Based upon official documents and several years of field research in Thinh Liet Commune, a Red River delta community near Hanoi, it provides the first detailed account of the nature of revolutionary cultural reforms in Vietnam as how those reforms continue to animate contemporary socio-cultural life. The study examines the key foci of revolutionary cultural change, such as the articulation of a new moral system, the attempts to eliminate explanations that invoke supernatural causality, the creation of socialist weddings and funerals, and the development of innovation ties to commemorate war dead. By examining debates over culture, ritual, and morality that have emerged between residents, notably between men and women, and party members and non-party members, the study shows how ideas and values that preceded the revolution have entered into a creative dialogue with those that were articulated by the revolution, and how this has produced an innovative set of ritual and other practices, particularly since the relaxation of the cultural reform agenda in the post-1986 period.